Utilization of Webinars and Live Instagram As Tokocrypto Marketing Communication Media - Muhammad Rif’at Al-Razi; Betty Tresnawaty; Jenny Ratna Suminar; Nindi Aristi (Communicatus: Jurnal Ilmu komunikasi, 2022)
Employers' use of communication technology is practical, fast, efficient, and effective. Among the communication technology tools that can be used to support business activities are the Zoom application, Google Meet for webinars, and social media such as Instagram, which is used as a marketing medium. This study aims to determine the use of webinars and live Instagram as a medium of business communication in Tokocrypto marketing. This research uses a qualitative approach with a case study approach. The study results show that, First, during the Covid-19 Pandemic, online media such as webinars and live Instagram were very effective as a medium for Tokocrypto's marketing communications. Using online media is one of the best ways to reach an audience. Applications used by Meeting, Youtube, and Instagram by Tokocrypto as a platform for buying and selling cryptocurrency assets. This is a convenience during a pandemic like today. Second, Tokocrypto utilizes webinars and live Instagram as a means of creativity in promoting, marketing, and educating cryptocurrencies on the Tokocrypto platform, with exciting material, competent sources, and dible guest stars so that Tokocrypto can create an ecosystem for users or Tokocrypto. Third, Tokocrypto was able to effectively and efficiently utilize webinars and live Instagram in publishing to audiences during the Covid-19 Pandemic.Â